2022
DOI: 10.1021/acs.jcim.2c01185
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative Assessment of Molecular Geometries and Energies from the Open Force Field

Abstract: Force fields form the basis for classical molecular simulations, and their accuracy is crucial for the quality of, for instance, protein–ligand binding simulations in drug discovery. The huge diversity of small-molecule chemistry makes it a challenge to build and parameterize a suitable force field. The Open Force Field Initiative is a combined industry and academic consortium developing a state-of-the-art small-molecule force field. In this report, industry members of the consortium worked together to objecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 64 publications
0
29
0
Order By: Relevance
“…Zhu showed similar results in its benchmark calculations of ligands FFs when compared to experimental osmotic coefficient data . Amore et al demonstrated that different FFs provide varying conformer energies and geometries during the optimization of multiple molecules and fragments . We documented that the parametrization of benzamidine using default GAFF parameters led to unsatisfactory outcomes, altering the ligand binding conformation and the free-energy landscape of the benzamidine/trypsin binding process .…”
Section: Friendliness and Performancementioning
confidence: 53%
See 1 more Smart Citation
“…Zhu showed similar results in its benchmark calculations of ligands FFs when compared to experimental osmotic coefficient data . Amore et al demonstrated that different FFs provide varying conformer energies and geometries during the optimization of multiple molecules and fragments . We documented that the parametrization of benzamidine using default GAFF parameters led to unsatisfactory outcomes, altering the ligand binding conformation and the free-energy landscape of the benzamidine/trypsin binding process .…”
Section: Friendliness and Performancementioning
confidence: 53%
“…An accurate estimate of kinetic rates requires a proper identification of TSs . However, subpar parameters might overly stabilize specific ligand (and protein) conformations, thus altering the identification and energetic evaluation of metastable and transient states. , It has been shown that inadequacies in the van der Waals and electrostatic terms of FFs may influence partition functions, , and also impact the osmotic coefficients of some chemical entities . Using the paradigmatic system benzamidine/trypsin, we have recently shown that proper parametrization of the ligand torsional potentials is essential to reconstruct the correct ligand binding conformation and free-energy surface .…”
Section: Force Fieldsmentioning
confidence: 99%
“…Specifically, we use a set of QM optimized conformer geometries and energies to assess how well we can reproduce conformer energetics and geometries with MM parameters. A much larger data set of QM-optimized gas-phase geometries, named “OpenFF Industry Benchmark Season 1 v1.1” on QCArchive, is now used for benchmarking MM optimized geometries . We built this data set in collaboration with our industry partners to benchmark force fields more generally, and it consists of nearly 9847 unique molecules, and a total of 76713 conformers.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the Sage library contains 167 rotatable torsion parameters, compared to the 146 K of OPLS3e. 33,35 While this minimal parameter set does come with reduced accuracy compared to highly parameterised, proprietary force fields, 36 users can make use of OpenFF-BespokeFit 33 to fit bespoke torsion parameters to molecules of interest and improve agreement with QM data. The OpenFF software stack additionally includes robust tools, such as ForceBalance 19 and Evaluator, 20 which we have taken advantage of in the current study to automatically curate and train against thousands of experimental and quantum mechanical reference data points.…”
Section: Discussionmentioning
confidence: 99%